Which nation is best in Nordic elite sport? An analysis of the results of Denmark, Finland, Norway and Sweden in international elite sport - past and present - Andersen, M. (2018)
This article focuses on elite sport in Denmark, Finland, Norway and Sweden, from historical and current perspectives. These Nordic nations have far more similarities than dissimilarities. They are all strong welfare models. Frequently, the model of Nordic welfare is admired by people, both inside and outside the Nordic nations. This model forms values, standards, structures and organization of a number of areas in the societies, including sport for all and elite sport. All four nations rank high in international comparison of e.g. economy, education, health or trust in public authorities. But how well do the nations perform, globally and among each other when it comes to elite sport? Why have they chosen four different elite sport models? Which nations prioritize winter sports, and which prioritize summer sports. And what sports - Olympic or non-Olympic - are the most competitive in each nation? These questions are attempted answered in the following pages.